TÂM CỦA NGUYỄN DU TỪ THƠ CHỮ HÁN ĐẾN VĂN CHIÊU HỒN - Nguyễn, Cảnh Chương (Đại học Đà Lạt, 2023)
From Chinese poetry,“The Tale of Kieu”to “Van chieu hon” shows a movement in Nguyen Du’s thought. The mind of Nguyen Du moved from the heart of a Confucian,in which Chinese poetry expressed life’s pains and sorrows, to the immense compassionate heart of Buddhism for sentient beings in “Van chieu hon”.This article highlights that movement. At the same time, it is clear that, whether from the mind of the scholar Nguyen Du, or the mind of the Buddhist disciple Nguyen Du, the movement in Nguyen Du’s thought is also derived from a kind heart: a "thinking heart for a thousand years" of the great Vietnamese national poet.